Magnetic resonance imaging findings of the proximal metacarpus in Quarter Horses used for cutting: Retrospective analysis of 32 horses 2009–2012. (21st September 2017) - Barrett, M. F.; Manchon, P. T.; Hersman, J.; Kawcak, C. E.
Summary: Background: Injury to the proximal suspensory ligament is a common cause of lameness in cutting horses. Radiographic and ultrasonographic imaging of lesions responsible for lameness can provide ambiguous results. MRI provides the most comprehensive diagnostic imaging evaluation of lesions specifically affecting cutting horses. Objectives: To describe the distribution and severity of bone and soft tissue lesions present in the proximal metacarpus of Quarter Horse cutting horses and to assess the impact of these lesions on return to competition. Study design: Retrospective case series. Methods: Retrospective analysis of 32 cutting horses referred for MRI of the proximal metacarpus between 2009 and 2012 with a 2‐year follow‐up period. MRI studies were evaluated by a board‐certified veterinary radiologist; the severity of lesions was graded from 0 (absent) to 3 (severe). Results: A total of 20 right and 24 left forelimbs (12 bilateral studies) of 32 horses were evaluated. The most common findings were: third metacarpal (McIII) sclerosis at the proximal suspensory ligament (PSL) origin (42/44), McIII resorption at the PSL origin (32/44), PSL dorsal margin fibre irregularity (30/44) and McIII bone contusion (22/39). Of the 30 horses, 22 horses successfully returned to competition, irrespective of severity of injury. Strong correlation exists between the degree of resorption in the palmar cortex of proximal McIII, degree of McIII sclerosis and severity of dorsal margin fibre irregularity. Main limitations: Statistical significance was limited by small study population. Further analysis of prognosis was limited by availability of comprehensive medical records. Conclusions: Cutting horses with proximal metacarpal pain have significant pathological change within the proximal suspensory ligament and its enthesis on the palmar cortex of McIII. Severity of lesions and degree of lameness at the time of diagnosis does not influence return to performance. Accurate diagnosis of proximal metacarpal lesions based on MRI offers clinicians the capacity to select treatment protocols targeted to each disease process.